Separation of Plasminogen Activators from Human Plasma and a Comparison with Activators from Human Uterine Tissue and Urine - Kok, Preben (Thrombosis and Haemostasis, 1979)
Normal human plasma contains acid-stable as well as labile plasminogen activators. The activity of activators in plasma euglobulins was inhibited by EACA in an uniform pattern, similar to that obtained with the major activators in human uterine tissue or with the purified porcine tissue activator, but different from the patterns obtained with plasmin or with urokinase.Gel filtration at high ionic strength separated activators corresponding to particle sizes of 60,000 dalton and about 10,000 dalton, corresponding to two activators similarly obtained from human tissue. The 60,000 dalton activator was precipitated in the euglobulin fraction. Its concentration increased in plasma after exercise. The 10,000 dalton activator was found mainly in the supernatant. Gel filtration in 0.15 M solutions yielded activators in fractions of molecular sizes of 100-140,000 dalton and 200,000 dalton or larger.The activity of normal and exercise euglobulins was inhibited by antiserum to a plasminogen activator prepared from porcine tissue, but it was not inhibited by antiserum to urokinase. Plasminogen activators in human plasma euglobulins resembled immunochemi- cally the activators in human uterine tissue.